2019
DOI: 10.1111/1750-3841.14735
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Human Enteric Adenoviruses in Fresh Tropical Seafood from Retail Markets and Landing Centers

Abstract: Human adenoviruses (HAdVs) are the foodborne enteric pathogens transmitted by the consumption of contaminated shellfish. In this study, the occurrence of enteric adenoviruses in finfish and shellfish was investigated by virus concentration and polymerase chain reaction (PCR). Total plate count, total coliform, and fecal coliform levels were determined and correlated with the presence of adenovirus. Samples of fish, bivalve mollusks, crustaceans, and cephalopods were collected from supermarkets, landing centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…In our study, HAdV was the second most frequently detected virus. Few studies have reported the presence of HAdV in shellfish, with similar or higher detection rates than ours such as in India, where authors detected HAdV DNA in 21.3% of seafood samples analyzed from retail markets of Mumbai [14]. In Japan, HAdV was found in 52% of the packages of clams [82].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, HAdV was the second most frequently detected virus. Few studies have reported the presence of HAdV in shellfish, with similar or higher detection rates than ours such as in India, where authors detected HAdV DNA in 21.3% of seafood samples analyzed from retail markets of Mumbai [14]. In Japan, HAdV was found in 52% of the packages of clams [82].…”
Section: Discussionsupporting
confidence: 75%
“…In recent years, reports of foodborne illnesses of viral origin have increased significantly, and bivalve mollusks are one of the main food groups implicated in outbreaks of acute gastroenteritis (AGE) or hepatitis [12,13]. Norovirus and hepatitis A (HAV) are the most common associated viruses; however, other viral agents, including rotavirus A (RVA), human adenovirus (HAdV), human bocavirus (HBoV), enterovirus, sapovirus, and astrovirus have been detected and/or implicated in foodborne diseases [14][15][16][17][18][19][20][21][22]. Aquaculture production of bivalve mollusks is mainly performed in open seawater systems, where they are exposed to any pollutant present in the seawater (enteric viruses, bacteria and microplastics) during their growth [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Fusco et al [ 48 ] reported the frequency of 5.6% of human mastadenovirus in bivalve samples collected in coastal areas of the Campania region in Southwestern Italy from 2015 to 2017. In Mumbai, India, the incidence of human mastadenovirus in seafood from different landing centers and markets was 21%, with the highest incidence in clam samples (14.9%) [ 88 ]. Besides that, several environmental studies in Brazil have demonstrated high frequencies of the human mastadenovirus in coastal waters, lagoons, and bivalves [ 73 , 89 , 90 , 91 , 92 ].…”
Section: Discussionmentioning
confidence: 99%